Act of Feb. 4, 1812, 195 Del. Laws 522 (1812). - (:unkn) unknown (General Publisher, 1812)
An Act to prevent the discharging of fire-arms within the towns and villages, and other public places within this State, and for other purposes.
--
Keywords: DISCHARGE